Enhancing Arabic Speaking Proficiency through Digital Collaborative Platforms: The Impact of Miro Brainstorm at MAN 1 Serang - Rena Sri Meilani; Rosidah Rosidah (Fakultas Tarbiyah dan Keguruan, 2025)
Purpose – This study investigates the influence of Miro Brainstorm, a digital collaborative whiteboard, on the Arabic speaking skills (maharah al-kalam) of tenth-grade students at MAN 1 Serang. Addressing the challenges of conventional rote-memorization methods and high language anxiety in Indonesian secondary schools, this research aims to evaluate whether visual-collaborative scaffolding can significantly improve communicative competence. Design/methods/approach – Utilizing a quasi-experimental design, the study involved 64 students divided into experimental (N=33) and control (N=31) groups. Data were collected through pre-tests, post-tests, observations, and interviews, then analyzed using descriptive statistics and linear regression. Findings – The results indicate a substantial improvement in the experimental group, with mean scores rising from 42.91 to 81.06. Regression analysis yielded an R-Square value of 0.807, demonstrating that the use of Miro Brainstorm accounts for 80.7% of the variance in students' speaking proficiency (p < 0.05). Research implications – These findings imply that digital brainstorming tools serve as effective cognitive scaffolds that reduce cognitive load and stimulate verbal productivity by visualizing abstract linguistic concepts. However, this study is limited by its specific focus on a single grade level and short-term intervention. It is recommended that future research explores the long-term retention of these gains and the platform's efficacy across other linguistic skills, such as writing and listening, within broader educational contexts.